The epigean pseudoscorpions of the genus Neobisium from Corsica and Sardinia, with description of a new species (Pseudoscorpiones: Neobisiidae) - Gardini, Giulio; Gardini, Pietro (Zootaxa, 2025)
A taxonomic revision of the epigean species of Neobisium (Neobisium) Chamberlin, 1930 from Corsica and Sardinia is proposed and a key is provided that also includes the subterranean species from the same geographical area. The new species Neobisium (Neobisium) knoflachae n. sp. (♂♀, loc. typ.: Corsica, Calvi, Forêt de Bonifatu, Bocca di Erbaghiolu) is described. Neobisium (Neobisium) gennargentui Callaini, 1983 (n. stat.) and Neobisium (Neobisium) major Callaini, 1982 (n. stat.) are elevated from subspecies of Neobisium (Neobisium) bernardi Vachon, 1937 and Neobisium (Neobisium) mahnerti Heurtault, 1980, respectively.